Maternal eating disorder history and toddlers' neurodevelopmental outcomes: A brief report. Issue 2 (14th March 2016) - Sadeh-Sharvit, Shiri; Levy-Shiff, Rachel; Lock, James D.
ABSTRACT: This study explored the neurodevelopmental outcomes of toddlers whose mothers have eating disorder histories and the contribution of maternal eating and comorbid psychopathology to the children's cognitive functioning. Twenty-nine mothers with prenatal eating disorders and their toddlers (18–42 months old) were compared to a case-control matched group of mothers with no eating psychopathology and their toddlers. Measures included current maternal eating and co-occurring psychopathology, and a developmental assessment of each child. The children of mothers with eating disorders showed delayed mental and psychomotor development. Severity of maternal eating disorder symptoms emerged as a significant predictor of child development, but other maternal psychopathology did not. Findings suggest that maternal eating disorder history may play a unique role in the development of neurodevelopmental functions in their children.